1,3-PROPANEDIOL: STATISTICAL OPTIMIZATION OF MEDIUM TO IMPROVE PRODUCTION BY Clostridium beijerinckii DSM 791 - Wischral, Daiana (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2015)
Biodiesel is a promising alternative biofuel, and as its production increases, so does production of the principal co-product, glycerol. The present study is aimed at maximizing the glycerol consumption and 1,3-propanediol (1,3-PDO) production by C. beijerinckii DSM 791, using sequential experimental design methodology for optimization of nutrients concentration for the fermentation medium. Three sequential experimental designs were performed: Plackett-Burman, fractional factorial and central composite rotational. The following nutrients of the medium were evaluated: urea, yeast extract, C2H3NaO2, KH2PO4, K2HPO4, MgSO4.7H2O, MnSO4.H2O, FeSO4.7H2O, glycerol, butyric acid, glucose and CaCO3. Urea, KH2PO4, MgSO4.7H2O, MnSO4.H2O, FeSO4.7H2O, butyric acid, glucose and CaCO3 were removed from the medium optimization since they had an insignificant statistical effect on 1,3-PDO production. The optimal concentrations of yeast extract, C2H3NaO2, K2HPO4 and glycerol predicted by the optimization were as follows (g/l): 0.5, 0.005, 5 and 8, respectively, which were validated experimentally. Desirability function allows the maximization of the 1,3-PDO production and percentage glycerol consumption simultaneously, which resulted in yield of 0.58 mol/mol of 1,3-PDO and 100 % of glycerol consumption. The results showed that the use of sequential experimental design and the use of the desirability function led to the optimization of the 1,3-PDO fermentation by C. beijerinckii DSM 791.